2016
DOI: 10.1371/journal.pone.0154353
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Population Structure in South African, French and Argentinian Angora Goats from Genome-Wide SNP Data

Abstract: The Angora goat populations in Argentina (AR), France (FR) and South Africa (SA) have been kept geographically and genetically distinct. Due to country-specific selection and breeding strategies, there is a need to characterize the populations on a genetic level. In this study we analysed genetic variability of Angora goats from three distinct geographical regions using the standardized 50k Goat SNP Chip. A total of 104 goats (AR: 30; FR: 26; SA: 48) were genotyped. Heterozygosity values as well as inbreeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
43
4
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 35 publications
15
43
4
4
Order By: Relevance
“…The panel was developed from sequence data from Saanen, Alpine, Creole, Boer, Kacang, and Savanna animals (http://www.goatgenome.org/). The genetic diversity measures observed in these nine populations are in agreement with estimates reported in the literature [15, 67, 68]. For instance, Nicoloso et al [15] reported levels of P N , H O , H E and F EH ranging from 0.951 to 0.997, 0.35 to 0.41, 0.35 to 0.41 and −0.06 to 0.070, respectively, for 14 Italian goat breeds using the same SNP chip.…”
Section: Discussionsupporting
confidence: 90%
“…The panel was developed from sequence data from Saanen, Alpine, Creole, Boer, Kacang, and Savanna animals (http://www.goatgenome.org/). The genetic diversity measures observed in these nine populations are in agreement with estimates reported in the literature [15, 67, 68]. For instance, Nicoloso et al [15] reported levels of P N , H O , H E and F EH ranging from 0.951 to 0.997, 0.35 to 0.41, 0.35 to 0.41 and −0.06 to 0.070, respectively, for 14 Italian goat breeds using the same SNP chip.…”
Section: Discussionsupporting
confidence: 90%
“…); and a variety of Angora goat populations in Argentina, France and South Africa (Visser et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Although the Angora breed in France is the result of a second wave of imports during the 1980s from several regions of the world (Canada, Texas, South Africa, Australia and New Zealand; Visser et al . ), it forms a homogeneous cluster of individuals. This is most likely due to the absence of later imports and its management in an efficient breeding program, which generally leads to homogenize within‐breed diversity.…”
Section: Discussionmentioning
confidence: 99%